2020
DOI: 10.1016/j.ensci.2020.100270
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine pathway in Parkinson's disease—An update

Abstract: Parkinson's disease (PD) is a complex multi-factorial neurodegenerative disorder where various altered metabolic pathways contribute to the progression of the disease. Tryptophan (TRP) is a major precursor in kynurenine pathway (KP) and it has been discussed in various in vitro studies that the metabolites quinolinic acid (QUIN) causes neurotoxicity and kynurenic acid (KYNA) acts as neuroprotectant respectively. More studies are also focused on the effects of other KP metabolites and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 120 publications
(167 reference statements)
0
48
0
1
Order By: Relevance
“…It was shown in animal studies that increased levels of QUIN and 3-HK can be found in both the brain and plasma [ 160 ]. Both KAT-I and KAT-II activity was lower in the plasma of PD patients, resulting in a lower level of KYNA observed [ 161 ]. Some studies found reduced levels of KYNA in the cortical regions and the basal ganglia of PD patients [ 162 ].…”
Section: Kynurenines As Biomarkers For Progression and As Possible Therapeutic Targetsmentioning
confidence: 99%
“…It was shown in animal studies that increased levels of QUIN and 3-HK can be found in both the brain and plasma [ 160 ]. Both KAT-I and KAT-II activity was lower in the plasma of PD patients, resulting in a lower level of KYNA observed [ 161 ]. Some studies found reduced levels of KYNA in the cortical regions and the basal ganglia of PD patients [ 162 ].…”
Section: Kynurenines As Biomarkers For Progression and As Possible Therapeutic Targetsmentioning
confidence: 99%
“…Various metabolomics studies have been performed to identify specific targets and biomarkers in PD pathogenesis. The metabolism of tryptophan (TRP) in association with the kynurenine pathway (KP) has been employed in multiple neurodegenerative and psychiatric diseases, cancer, inflammation, obesity, and diabetes [8]. The metabolites linked to KP are responsible for exerting physiological actions by interacting with intracellular or extracellular receptors in the peripheral and central nervous system (CNS) regions [8].…”
Section: Introductionmentioning
confidence: 99%
“…The metabolism of tryptophan (TRP) in association with the kynurenine pathway (KP) has been employed in multiple neurodegenerative and psychiatric diseases, cancer, inflammation, obesity, and diabetes [8]. The metabolites linked to KP are responsible for exerting physiological actions by interacting with intracellular or extracellular receptors in the peripheral and central nervous system (CNS) regions [8]. The activity at α7 nicotinic acetylcholine receptors and glutamate receptors is regulated by KP metabolites, which in turn influences the excitatory neurotransmission [9,10] and can further affect the immune-mediated responses, by acting at the transcription factor aryl hydrocarbon receptor (AhR) [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kynurenine-3-monooxygenase (KMO, in the past also referred to as kynurenine-3-hydroxylase), has emerged as a therapeutic target for the treatment of numerous neurological disorders including Alzheimer’s disease (AD) [ 1 , 2 , 3 ], Huntington’s disease (HD) [ 4 , 5 ], Parkinson’s disease (PD) [ 6 ], schizophrenia [ 7 , 8 , 9 ], depression [ 10 , 11 ], and neuropathic pain [ 12 , 13 , 14 ] and its inhibition has been found to be protective against cancer [ 15 ] and multiple organ disorder in acute pancreatitis [ 16 ]. Located at a critical branch point in the main metabolic pathway of L-tryptophan, KMO facilitates the hydroxylation of L-kynurenine (L-kyn) to 3-hydroxy-kynurenine (3-HK) as opposed to the kynurenine aminotransferase (KAT) branch, which catalyzes the cyclization of L-kyn to form kynurenic acid (KynA) ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%